Evaluation of Japanese Language Proficiency in Online Internships for Vocational School Students of Diponegoro University, Semarang - Maharani Patria Ratna; Arsi Widiandari (IZUMI, 2021)
The internship is one of the five-semester compulsory courses for D3 (Diploma 3) students of the Diponegoro University Vocational School, Semarang. Internships are held for a minimum of 3 months in the industry. Internships are applied at the diploma education level to allow the student to be well prepared before entering the world of work after graduating. This study aimed to evaluate the use of Japanese in online internships. The online internship has been applied since the pandemic of Covid-19. This research is expected to be a self-evaluation for curriculum adjustments to answer industry needs. Mainly because the Diponegoro University Vocational School no longer accepts D3 level students since 2019. In 2019, The D4 (Diploma 4) program replaced the closure of the D3 program. Of course, this makes curriculum adjustment a very urgent matter. Therefore, we need an evaluation of the curriculum implemented at the D3 level as a reference. This research is a qualitative descriptive study with a survey method. The data was collected through a survey distributed to 5 Japanese Vocational School (SV) D3 students who did online internships using Japanese. The survey contains several questions covering the four language skills: speaking, listening, reading, and writing. The survey was carried out online by providing three alternative answers to multiple-choice questions circulated via a google sheet. Based on the research results, it can be understood that students are pretty satisfied with the abilities obtained during lectures because they can be applied during online internships using Japanese. Students still experience dissatisfaction with one aspect of Japanese language learning, which is the Speaking aspect. As a result, it becomes an obstacle when doing online internships. However, this percentage of dissatisfaction is minor compared to other aspects of learning. It is an important point that can reference self-evaluation of study programs, both for curriculum preparation and classroom teaching.